Investigating the thermal, mechanical and thermal cyclic properties of plasma-sprayed Al2O3-7YSZ/7YSZ double ceramic layer TBCs - Han, Jiasen; Zou, Yong; Wu, Dongting; Zhang, Yongang (Journal of the European Ceramic Society, 2023)
Double ceramic layer (DCL) TBCs consisting of a top 20 wt.% Al2O3-7YSZ layer and a bottom 7YSZ layer were desirably designed to achieve preferable performance while the thermal, mechanical and thermal cyclic properties were comprehensively investigated. Compared to the conventional 7YSZ TBCs, the thermal insulation properties of the DCL coating were significantly improved due to the increased oxygen vacancy concentration induced by Al2O3 addition while the thickness of the thermally grown oxides was diminished by the decreased oxygen diffusion rate. Furthermore, the improved fracture toughness of the DCL coating also prolonged the thermal cyclic life.